PEMETAAN MANGROVE DALAM BENTUK WEBGIS (STUDI KASUS : MUARA GEMBONG) - Fawaz Fawaz; Ribka Jelita Nababan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2021)
Muara Gembong is an area in Bekasi Regency, has a huge mangrove potential and spread on the coast. But in reality the mangrove forests in Muara Gembong are degraded every year. In order to know the impact of degradation caused by residential land, cultivation ponds need mapping to further overcome the problem. How to map it using remote sensing and webgis. The purpose of this study is to produce mangrove mapping webgis applications that users can access in internet browsers with pages (www.upi.asia). This application can display information about mangrove mapping, Bekasi city mapping, maker information, application maker contacts, overall zoom information of Bekasi City, information about legends, downloading Bekasi maps and mangrove mapping and literature menu in the form of blogs for general information about mangroves. Webgis creation uses several methods and creation applications such as the Google Maps API. Leaflet.js, CodeIgniter and MySQL as databases. Mapping process used latitude and longitude from Google Maps, this is to facilitate coding in the process of webgis creation. The application was successfully run using computers and smartphones, and a stability test on 10 respondents that contained about the effectiveness of the application, user ease and user satisfaction. Based on the results of questionnaires conducted by mangrove mapping webgis application is quite effective and easy to use by users. Keywords: Framework CodeIgniter, Google Maps API, Leaflet js, Webgis.